2023
DOI: 10.3389/fpubh.2023.1138915
|View full text |Cite
|
Sign up to set email alerts
|

Nature visits during the COVID-19 pandemic in Norway: Facilitators, motives, and associations with sociodemographic characteristics

Abstract: IntroductionThe COVID-19 pandemic has been linked to increased mental health issues and reduced well-being. Researchers also reports increased frequency of nature visits during the pandemic, proposing it may mitigate some of these negative consequences. Using the case of Norway, a country with ample access to nature and relatively low levels of pandemic-related restrictions, this study sought to (i) understand how the COVID-19 crisis impacted patterns of nature visits and specific nature-based activities, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In subsequent studies conducted after the second coronavirus wave in Italy (May-June 2021), a 7.7% increase was observed in the frequency of use of UGS sites close to home, and a 16.5% decrease was observed in the percentage of those who reported visiting a UGS once a week [71]. A survey on the adult population in Norway conducted by Litleskare and Calogiuri et al [28] found that 32% of respondents decide to relax in green spaces more often and 12% less often. Among respondents, women, younger people, and people from higher-income households increased their activity.…”
Section: Mobility Of Society and Demand For Recreation In Naturementioning
confidence: 99%
See 4 more Smart Citations
“…In subsequent studies conducted after the second coronavirus wave in Italy (May-June 2021), a 7.7% increase was observed in the frequency of use of UGS sites close to home, and a 16.5% decrease was observed in the percentage of those who reported visiting a UGS once a week [71]. A survey on the adult population in Norway conducted by Litleskare and Calogiuri et al [28] found that 32% of respondents decide to relax in green spaces more often and 12% less often. Among respondents, women, younger people, and people from higher-income households increased their activity.…”
Section: Mobility Of Society and Demand For Recreation In Naturementioning
confidence: 99%
“…Thus, the volume of visitation in UGS and forest areas was controlled by national or regional regulations. Litleskare and Calogiuri [28], regarding the reasons for the increase in the number of visits, mentioned the effects of constraints, such as the following: seeking an alternative way of spending time in relation to the gym and sporting events, more free time, more "flexible days", more free time with family and friends, remote work and learning. Regarding the motives, they mentioned the desire to play sports and stay physically active, to meet family and friends, to reduce stress and dispel worries, to deal with the pandemic reality, as well as the need to find peace and quiet.…”
Section: Mobility Of Society and Demand For Recreation In Naturementioning
confidence: 99%
See 3 more Smart Citations